The Role of Artificial Intelligence in Smart Classes: A survey - Dimitriadou, Eleni A.; Lanitis, Andreas (My University, 2022)
During the years, the concept of Smart Classroom' evolved to reflect technological advances. This survey provides a review of research work on smart classroom technologies, with a focus on emerging and Artificial Intelligence(AI)-related technologies. Smart classroom technologies related to the effective class management that enhance the convenience of classroom environments, the use of teaching aids during the educational process and the use of performance assessment technologies are presented. Apart from discussing the range of technological achievements in each of the aforementioned areas, the role of AI is thoroughly discussed allowing researchers and developers in AI to realize the existing uses of AI in smart classes and get informed about future perspectives and challenges in adopting AI-based techniques in smart classes.
Keywords: Artificial intelligence; Emerging technologies; Smart classroom